Layered Double Hydroxides as Effective Adsorbents for U(VI) and Toxic Heavy Metals Removal from Aqueous Media - G. N. Pshinko (Journal of Chemistry)
Capacities of different synthesized Zn,Al-hydrotalcite-like adsorbents, including the initial carbonate [Zn4Al2(OH)12]·CO3·8H2O and its forms intercalated with chelating agents (ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), and hexamethylenediaminetetraacetic acid (HMDTA)) and heat-treated form Zn4Al2O7, to adsorb uranium(VI) and ions of toxic heavy metals have been compared. Metal sorption capacities of hydrotalcite-like adsorbents have been shown to correlate with the stability of their complexes with the mentioned chelating agents in a solution. The synthesized layered double hydroxides (LDHs) containing chelating agents in the interlayer space are rather efficient for sorption purification of aqueous media free from U(VI) irrespective of its forms of natural abundance (including water-soluble bi- and tricarbonate forms) and from heavy metal ions. [Zn4Al2(OH)12]·EDTA·nH2O is recommended for practical application as one of the most efficient and inexpensive synthetic adsorbents designed for recovery of both cationic and particularly important anionic forms of U(VI) and other heavy metals from aqueous media. Carbonate forms of LDHs turned out to be most efficient for recovery of Cu(II) from aqueous media with pH0≥7 owing to precipitation of Cu(II) basic carbonates and Cu(II) hydroxides. Chromate ions are efficiently adsorbed from water only by calcinated forms of LDHs.